2021
DOI: 10.1177/2331216520985678
|View full text |Cite
|
Sign up to set email alerts
|

No Evidence That Music Training Benefits Speech Perception in Hearing-Impaired Listeners: A Systematic Review

Abstract: As musicians have been shown to have a range of superior auditory skills to non-musicians (e.g., pitch discrimination ability), it has been hypothesized by many researchers that music training can have a beneficial effect on speech perception in populations with hearing impairment. This hypothesis relies on an assumption that the benefits seen in musicians are due to their training and not due to innate skills that may support successful musicianship. This systematic review examined the evidence from 13 longit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 65 publications
0
10
0
Order By: Relevance
“…A decision tree and score calculator, to aid researchers and clinicians in the use of the MUSQUAV, is available in the Online Resource n3 [3]. Future longitudinal studies should assess the ability of the MUSQUAV to detect clinical changes in patients who underwent music focused intervention, including possible correlations with language and communication abilities, which have recently been debated [19,20]. The extension of music evaluation (including MUSQUAV questionnaire) and music focused interventions on people with mild hearing loss should also be considered, given the fact that hearing aids (HA) and CI share similar technologies-implication of bimodal hearingand patients often pass from hearing aids to CI during their lifetime due to the natural course of hearing loss diseases.…”
Section: Discussionmentioning
confidence: 99%
“…A decision tree and score calculator, to aid researchers and clinicians in the use of the MUSQUAV, is available in the Online Resource n3 [3]. Future longitudinal studies should assess the ability of the MUSQUAV to detect clinical changes in patients who underwent music focused intervention, including possible correlations with language and communication abilities, which have recently been debated [19,20]. The extension of music evaluation (including MUSQUAV questionnaire) and music focused interventions on people with mild hearing loss should also be considered, given the fact that hearing aids (HA) and CI share similar technologies-implication of bimodal hearingand patients often pass from hearing aids to CI during their lifetime due to the natural course of hearing loss diseases.…”
Section: Discussionmentioning
confidence: 99%
“…The Role of Music in Families Questionnaire (RMFQ) was developed to evaluate the role of music in families of children with hearing loss, and their general attitudes and level of engagement with music (Looi et al 2018, 2019). One section of the RMFQ (Childhood Music Participation and Experiences) was used in the present study to appraise the level of formal music participation and experience each participant had received before commencement of the present study.…”
Section: Methodsmentioning
confidence: 99%
“…Recent studies for children with hearing loss indicate preliminary evidence of positive associations between music, speech, and language outcomes such as singing, prosodic stress and reading (Torppa et al 2020), melodic contour identification and Mandarin lexical tone perception (Cheng et al 2018), piano instruction and prosody perception (Good et al 2017). However, it should be noted that a recent systematic review on the benefits of music training for individuals with hearing loss found the evidence to support speech perception benefits is not yet sufficiently robust, or demonstrated convincingly (McKay 2021).…”
Section: Introductionmentioning
confidence: 99%
“…This is owing to the fact that he is unable to use his hearing aids in his day-to-day life, which has a wide range of ramifications and a major influence on his life. According to McKay (2021) A child is also considered to have a hearing loss if they are unable to benefit from their hearing aids in their regular activities. When referring to a health issue, hearing loss and deafness are commonly interchanged since they describe the same thing.…”
Section: Introductionmentioning
confidence: 99%